Analisis Usaha Mikro, Kecil, dan Menengah (UMKM) di Kampung Batuhulung, Bubulak, Bogor - Karima Tazkia; Saidah Idah; I Wayan Astika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Bubulak Village is one of the villages in West Bogor District that located near the center of Bogor City. Easy access for transportation and it’s location that located near the city center are two factors that can be an opportunities for rural communities to empower rural economic through Micro, Small and Medium Enterprises (MSMEs). The purpose of writing this report is to identify problem and the alternative solution for the MSMEs located in Batuhulung Village, Bubulak Village, Bogor. The method that used to write the report was descriptive qualitative method and supported by primary and secondary data. The sample was determined through the Purposive Sampling method and the data was collected using interview and direct observations. There are two main problems that MSMEs Batuhulung Village face in order to develop themself. The first problem is capital and the second problem is the limited human resources.